Analysis of Tautomerism in β-Ketobuanamides by Nuclear Magnetic Resonance: Substituent, Temperature and Solvent Effects - Laurella, Sergio; Sierra, Manuel González; Furlong, Jorge; Allegretti, Patricia (Journal of Applied Solution Chemistry and Modeling, 2012)
β-ketoamides are versatile intermediates for the synthesis of several heterocycles and they are also relevant compounds in biological systems, with their tautomeric equilibria being a crucial aspect to be studied in order to understand their chemical and biological behaviour. Tautomeric equilibria of a series of β-ketobutanamides were analyzed by means of 1HNMR, determining that ketoamide and Z-enolamide are the main tautomeric species in solution, both presenting internal hydrogen bonds. Keto-enol equilibrium predominates over other possible tautomerisms (e.g. amide-imidol). The enol tautomer appears to be favoured by electron withdrawing substituents and non-protic solvents. Thermodynamic parameters ΔH and ΔS were determined in CDCl3 and DMSO-d6, showing that the keto-enol equilibria are exothermic and require a molecule order increase.